1983
DOI: 10.1042/cs0650539
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate and Lipid Metabolism during Continuous Ambulatory Peritoneal Dialysis (CAPD): The Effect of a Single Dialysis Cycle

Abstract: The effect on hormonal status and intermediary metabolism of a single 6 h dialysis cycle at two different concentrations of dialysate glucose was investigated in six patients on continuous ambulatory peritoneal dialysis. The basal blood glucose level was elevated by 0.5 mmol/l, associated with a threefold increase in basal serum insulin compared with seven normal controls. Blood glucose and serum insulin rose further during dialysis, particularly with hypertonic (215 mmol of glucose/l) dialysis fluid and level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…We standardized these procedures not only in a fasting state, but also after the overnight dwell with 1.36% glucose solution, before the PET. Such a protocol minimizes any potential effect of peritoneal glucose absorption, while allowing for dialysis maintenance, as a previous study by Heaton et al showed that there are no differences in fasting plasma glucose and insulin between undialyzed PD patients (with no PD solution in the abdomen) and patients on 1.36% glucose solution, after the first 60 minutes of a 1.36% glucose dwell (38). Assuming this, other investigators focused on metabolic issues, performing measurements after the 1.36% glucose solution overnight dwell (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…We standardized these procedures not only in a fasting state, but also after the overnight dwell with 1.36% glucose solution, before the PET. Such a protocol minimizes any potential effect of peritoneal glucose absorption, while allowing for dialysis maintenance, as a previous study by Heaton et al showed that there are no differences in fasting plasma glucose and insulin between undialyzed PD patients (with no PD solution in the abdomen) and patients on 1.36% glucose solution, after the first 60 minutes of a 1.36% glucose dwell (38). Assuming this, other investigators focused on metabolic issues, performing measurements after the 1.36% glucose solution overnight dwell (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…There is continuous absorp tion of dextrose from dialysis fluid, rapid at the start of the exchange but slower as the fluid concentration falls [6] so that after 6 h about 80% has been absorbed. This may contribute to an elevation of blood sugar, stimula tion of insulin secretion [14] and maintenance of high glycogen stores. Consequently, it is generally assumed that this carbohydrate may be useful in providing calories during periods of illness and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…CAPD patients showed the highest degree of glucose intolerance as compared to the nondialyzed uremic and the chronic-hemodialysis subjects. This finding could be related to the considerable daily glucose load to which CAPD patients are perma nently exposed [28]. It seems unlikely that residual glu cose from the last peritoneal exchange may have contrib uted to the higher glucose intolerance present in the CAPD group.…”
Section: Discussionmentioning
confidence: 74%